Impact of political risk on FDI revisited: an aggregate firm-level analysis - Vadlamannati, Krishna Chaitanya (International interactions, 2012)
Unlike previous studies on political risk and foreign direct investment (FDI) that used macro-level FDI data to test micro-level theories, I make use of aggregate data on U.S. firms' investment activities in 101 developing countries during the period 1997-2007 to reassess the propositions. Using a multilevel mixed-effects linear instrumental variable approach, I find that lower political risk is associated with (a) an increase in U.S. firms with equity stake of 51% and above, (b) a higher proportion of fixed assets, and (c) an increase in the return on investments, after controlling for a host of relevant factors. Further analysis reveals the relationship is also strong with respect to investments in total assets and sales. The results are robust to alternative data, instruments, and estimation techniques. These results bring to fore the multiple risk hedging strategies available for foreign firms operating in high risk environments.
Gesehen am 22.10.2018
Article was published online on 21 December 2011